The The Influence of Technology Acceptance Factors on Intention to Study via Online Learning Behavior between Generation Y and Z Individuals in Bangkok - Intuluck, Watit (Journal of Humanities and Social Sciences Thonburi University, 2022)
The purpose of the research study was to compare the influence of technology acceptance factors on the intention to study via online learning behavior between Generation Y and Z individuals in Bangkok during the COVID 19 pandemic. In this study, 275 samples of students in generations Z and Y were used. The research instrument, which included a total of 30 items and a Cronbach’s alpha coefficient of 0.9, was used for data collection. The relationship between performance expectancy, effort expectancy, social influence, and facilitating conditions affecting intention to study via online learning behaviors of students in the Bangkok. The study was examined using a hierarchical regression analysis to investigate the moderating effect of generation. The results showed that the younger generation perceived performance expectancy and effort expectancy as being higher than those of the older generation. Educational management should ensure that messages about the performance advantages of online study and the suitability of the online system are well received by the young targets to increase their intention to study online. At the same time, social influence and facilitating conditions should be standardized and well received by both generations.